Resgate da alma: estudo sobre a atuação da Assembleia de Deus no presídio Dr. Rorinildo da Rocha Leão (Palmares-PE). - Andrade, Wellington Silva de (2020)
In the midst of deprivation and other difficulties experienced by a person deprived of liberty, religion appears as an important instrument of re-socialization. For some, it is the only source of hope for achieving better days and freedom. In this perspective, the churches arrive at the prisons with the intention of saving souls, calming and helping people in an apparent state of abandonment, and with that they end up re-socializing re-educated from the religious conversion. In this sense, the Assembly of God church in the city of Palmares provides religious assistance in the local prison and has presented itself as an important collaborator of the State in this important process of recovery of people from the world of crime. The research explores the relationship between resocialization and religion in the prison environment, as well as their representations, and narrates the historical contexts relevant to the themes. The Dissertation shows how much religion influences the re-socialization of people deprived of their liberty, in order to be used with the objective of sowing, in the prison universe, messages of hope and peace, at the same time, of social criticism. Therefore, the work required intense bibliographic research in works, such as those by Foucault (2009), Baratta (1990) and Berger (1985-2017-2018) and document analysis, interviews with persons deprived of liberty, religious authority and prison staff were used. We sought to make a historical overview of the Assembly of God in Brazil and social inequalities, in addition to presenting a brief survey on the support given by the State to religious works within Pernambuco prisons.